The Impact of Islamic-Based Migrant Associations on the Indonesian Migrants in Nagoya, Japan - Dwiputra, Rakadipta Septian; Ayuputri, Ikacipta Mega (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2024)
As the number of Indonesian migrant workers and students heading to Japan rises, organizations dedicated to their support and integration have become increasingly significant. Among these, Islamic-based organizations, reflecting Indonesia's majority Muslim population, have garnered attention. A key player in this landscape is “Keluarga Muslim Indonesia” (KMI) in Nagoya, a vibrant organization that has been instrumental in aiding Indonesian Muslim migrants in and around Nagoya. This study adopts a qualitative research approach, incorporating social media analysis and semi-structured interviews, to delve into the contributions of KMI Nagoya. The findings highlight four pivotal aspects of KMI Nagoya's impact: the provision of various Islamic activities meet the religious needs of Indonesian Muslim migrants; the facilitation of social integration, helping migrants acclimate to Japanese culture; the offering of activities aimed at empowering women; and the engagement of second-generation migrants, ensuring they maintain a connection to Islamic and Indonesian traditions. This study underscores the multifaceted role of KMI Nagoya in supporting Indonesian Muslim migrants, marking it as a cornerstone of their successful integration into Japan.